4D‐Var for numerical weather prediction. (17th October 2020) - Bonavita, Massimo; Lean, Peter
Abstract : Schematic representation of the way incremental 4D‐Var solves the nonlinear minimisation problem. The full nonlinear cost function (thick blue line) is minimised through the minimisation of successive quadratic cost functions (thin black lines) obtained by linearisation of the cost function around successively more accurate guess fields (Plot courtesy of Sebastien Massart, European Centre for Medium‐Range Weather Forecasts).